Tuberculosis Mortality in the United States: Epidemiology and Prevention Opportunities - Beavers, Suzanne F.; Pascopella, Lisa; Davidow, Amy L.; Mangan, Joan M.; Hirsch-Moverman, Yael R.; Golub, Jonathan E.; Blumberg, Henry M.; Webb, Risa M.; Royce, Rachel A.; Buskin, Susan E.; Leonard, Michael K.; Weinfurter, Paul C.; et al. (Annals of the American Thoracic Society, 2018)
More information on risk factors for death from tuberculosis in the United States could help reduce the tuberculosis mortality rate, which has remained steady for more than a decade. To identify risk factors for tuberculosis-related death in adults. We performed a retrospective study of 1,304 adults with tuberculosis who died before treatment completion and 1,039 frequency-matched control subjects who completed tuberculosis treatment in 2005 to 2006 in 13 states reporting 65% of U.S. tuberculosis cases. We used in-depth record abstractions and a standard algorithm to classify deaths in persons with tuberculosis as tuberculosis-related or not. We then compared these classifications to causes of death as coded in death certificates. We used multivariable logistic regression to calculate adjusted odds ratios for predictors of tuberculosis-related death among adults compared with those who completed tuberculosis treatment. Of 1,304 adult deaths, 942 (72%) were tuberculosis related, 272 (21%) were not, and 90 (7%) could not be classified. Of 847 tuberculosis-related deaths with death certificates available, 378 (45%) did not list tuberculosis as a cause of death. Adjusting for known risks, we identified new risks for tuberculosis-related death during treatment: absence of pyrazinamide in the initial regimen (adjusted odds ratio, 3.4; 95% confidence interval, 1.9-6.0); immunosuppressive medications (adjusted odds ratio, 2.5; 95% confidence interval, 1.1-5.6); incomplete tuberculosis diagnostic evaluation (adjusted odds ratio, 2.2; 95% confidence interval, 1.5-3.3), and an alternative nontuberculosis diagnosis before tuberculosis diagnosis (adjusted odds ratio, 1.6; 95% confidence interval, 1.2-2.2). Most persons who died with tuberculosis had a tuberculosis-related death. Intensive record review revealed tuberculosis as a cause of death more often than did death certificate diagnoses. New tools, such as a tuberculosis mortality risk score based on our study findings, may identify patients with tuberculosis for in-hospital interventions to prevent death.